PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KETAHANAN PANGAN GUNA MENCAPAI DESA MANDIRI SEJAHTERA DI DESA RANCASUMUR, KECAMATANA KOPO, KABUPATEN SERANG-BANTEN - Mitri Nelsi; Irfan Rizka Akbar; Lily Setyawati Kristianti (Abdi Jurnal Publikasi, 2024)
The aim of Community Service activities is to implement one of the tri dharmas of higher education. Apart from that, it is hoped that with community service, the existence of higher education can make a major contribution to the development and application of science to society. The methods used in community service are in the form of counseling and coaching, namely apart from actions, processes and results or statements are better. In this case, it shows progress, increased growth, evolution of various possibilities, development or improvement of something. The results of community service obtained are community development and empowerment in increasing food security in order to achieve an independent, prosperous village in Rancasumur Village, Kopo District, Serang Banten Regency. The knowledge gained can be developed and disseminated to provide the best for the surrounding community.